2020
DOI: 10.1007/s42250-020-00123-w
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainable Chemicals: A Brief Survey of the Furans

Abstract: Whether it is in the textiles, paints and coatings, energy sector, polymers, plastics, woods, sugar chemistry, pharmacy, aerospace and the automotive industries, the multiplicity of applications of furans and their derivatives, have made steady, impressive, and progressive impacts over the last 9 decades. After World War II, due to the shift in focus towards the petroleum-based chemical feedstocks, research, and development studies of these impressive class of lignocellulosic-derived chemicals, slowed down mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 124 publications
(155 reference statements)
0
33
0
Order By: Relevance
“…In particular, methyl Isobutyl ketone was the main component at 450˚C, reaching 5.7%. The furan structure contains a heterocycle of four carbon atoms and one oxygen atom; it primarily results from hemicellulose decomposition and is probably produced from hexoses [44,45]. The furan yield, including furfural decreased with increasing temperature similarly [46].…”
Section: Plos Onementioning
confidence: 99%
“…In particular, methyl Isobutyl ketone was the main component at 450˚C, reaching 5.7%. The furan structure contains a heterocycle of four carbon atoms and one oxygen atom; it primarily results from hemicellulose decomposition and is probably produced from hexoses [44,45]. The furan yield, including furfural decreased with increasing temperature similarly [46].…”
Section: Plos Onementioning
confidence: 99%
“…Iroegbu et al [34] noted that the complex hetero-matrix constituents of lignocellulosic biomass comprising primarily of cellulose, lignin, and hemicellulose affords an array of possible derivative chemicals and fuels. It was also suggested that if efforts (including research, funding, and support) commensurate to those that have sustained fossil-based chemistry were redirected into biobased-chemistry, it would significantly accelerate the resolution of current sustainability challenges [34].…”
Section: Bamboo As a Sustainable Resource For Cellulose Hemicellulose And Ligninmentioning
confidence: 99%
“…Iroegbu et al [34] noted that the complex hetero-matrix constituents of lignocellulosic biomass comprising primarily of cellulose, lignin, and hemicellulose affords an array of possible derivative chemicals and fuels. It was also suggested that if efforts (including research, funding, and support) commensurate to those that have sustained fossil-based chemistry were redirected into biobased-chemistry, it would significantly accelerate the resolution of current sustainability challenges [34]. Moreover, as the approximate chemical constituents of bamboos are comparable to those of traditional woods, with the exception of bamboos' substantial alkaline extracts, ash, and silica components [149], bamboos offer a renewable and sustainable alternative for the augmentation of derivable lignocellulosic biomass materials, such as cellulose, hemicellulose, lignin, and other extractable constituents [90].…”
Section: Bamboo As a Sustainable Resource For Cellulose Hemicellulose And Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…Furan is a cyclic aromatic ether found in cigarette smoke and used in the production of resins [ 11 ] and some agrochemicals and pharmaceuticals. Obtaining furan from “green” inedible lignocellulosic biomass is one of the promising sustainable, and industrially applicable alternatives to various petroleum-derived chemicals [ 12 , 13 ]. Recently, investigations on the presence of furan in coffee, juices, soups, and canned fruits or vegetables has gained widespread attention [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%